Principles of applying international financial reporting standards in the preparation of consolidated financial statementsInternational financial reporting standards - Shakeyev, S.S.; Syzdykova, D.I. (BUKETOV BUSINESS REVIEW, 2017)
The article reviews the main international financial reporting standards used in the consolidated financial statements of corporate entities, i.e. features, main goals and requirements of standards. The objective of one of the main standards of the consolidated financial statements of IFRS 3 «Business combinations» is disclosed: the purpose of this standard is to increase the relevance, reliability and comparability of information on business combination and its consequences that the reporting entity presents in its financial statements. In addition, the main differences and assumptions of IFRS 10 «Consolidated Financial Statements», effective from January 1, 2013, from IAS 27 «Consolidated and Separate Financial Statements», which were effective until January 1, 2013, were analyzed. It is considered that the main purpose of this standard is to determine the principles for the presentation and preparation of consolidated financial statements in cases where the entity controls one or more other entities. Another standard that is used in the preparation of consolidated financial statements is IAS 28 «Investments in Associates and Joint Ventures». It is considered that the main purpose of this standard is to determine the rules for accounting for investments in associates and the requirements for applying the equity method when accounting for investments in associates and joint ventures.